Improvement from ixekizumab treatment in patients with psoriatic arthritis who have had an inadequate response to one or two TNF inhibitors. (20th January 2021) - Kirkham, Bruce; Sesin, Carlos; Gellett, Amanda M.; Sprabery, Aubrey T.; Lin, Chen-Yen; Turkiewicz, Anthony
Abstract: Objective: To evaluate the efficacy of ixekizumab (IXE), a monoclonal antibody selectively targeting interleukin-17A, in patients with inadequate response to one or two TNF inhibitors (TNFi). Methods: A phase 3 study (SPIRIT-P2; NCT02349295) randomized patients with PsA with inadequate response or intolerance to one or two TNFi to receive 80-mg IXE every 2 weeks ( n = 123) or every 4 weeks ( n = 122) after a 160-mg starting dose or placebo (PBO; n = 118) through week 24. This post hoc analysis used data from inadequate responders to one or two TNFi, measuring the percentage achieving: ≥50% improvement in ACR response criteria (ACR50) and 100% improvement from baseline in the Psoriasis Area and Severity Index (PASI 100), ACR50, improvement in HAQ-Disability Index (HAQ-DI) ≥0.35, minimal disease activity (MDA), European League Against Rheumatism (EULAR) Good Response Criteria [improvement in Disease Activity Score 28 CRP (DAS28-CRP) >1.2], and Disease Activity in PsA (DAPSA) ≤14. Results: There were no significant differences in baseline characteristics between inadequate responders to one and two TNFi. At week 24, significantly more patients irrespective of previous TNFi experience receiving IXE than PBO achieved ACR50, HAQ-DI ≥0.35 improvement, MDA, EULAR good response, and DAPSA ≤14, and significantly more patients with inadequate response to one TNFi receiving IXE than PBO achieved ACR50 and PASI 100. Improvement persisted in all measures through week 52. Conclusion: IXE improved the signs and symptoms of PsA in a population of difficult-to-treat patients with inadequate response to one or two TNFi.